International spinal cord injury urodynamic basic data set (version 2.0). (December 2018) - Pannek, Jürgen; Kennelly, Michael; Kessler, Thomas; Linsenmeyer, Todd; Wyndaele, Jean-Jacques; Biering-Sørensen, Fin
Abstract Study design: Revision, review, and presentation of the International Spinal Cord Injury (SCI) Urodynamic Basic Data Set (version 2.0). Objectives: Describe the revision and review and present the dataset. Setting: International. Methods: The first version of the dataset was revised according to new knowledge and suggestions. The review included International SCI Data Sets Committee, American Spinal Injury Association (ASIA) board, International Spinal Cord Society (ISCoS) executive and scientific committees, major organizations, and interested individuals. The dataset was also on ASIA and ISCoS websites. All replies were answered and appropriate adjustments made. Finally, the dataset was endorsed by ASIA board, and ISCoS executive and scientific committees. Results: Among revisions are adoptions of new terminology by the International Continence Society. The variable "Detrusor function" has been divided into "Detrusor function during filling cystometry" and "Detrusor function during voiding". The response categories have been adjusted, deleting 'Not applicable' for the variables "Detrusor leak point pressure during filling cystometry", "Cystometric bladder capacity during filling cystometry" and "Urethral function during voiding". The cutoff-value for low bladder compliance has been modified from 10 mL/cm H2 O to 20 mL/cm H2 O. Conclusions: The International SCI Urodynamic Basic Data Set (version 2.0) with its complete syllabus is available fromhttp://www.iscos.org.uk/international-sci-data-sets .